Cloud data assured deletion scheme based on overwrite verification - Ruizhong DU; Pengliang SHI; Xinfeng HE (Tongxin xuebao)
At the end of data life cycle,there is still a risk of data leakage,because mostly data which was stored in cloud is removed by logical deletion of the key.Therefore,a cloud data assured deletion scheme (WV-CP-ABE) based on ciphertext re-encrypt and overwrite verification was proposed.When data owner wants to delete the outsourced data,the data fine-grained deletion operation was realized by re-encrypting the ciphertext to change the access control policy.Secondly,a searchable path hash binary tree (DSMHT) based on dirty data block overwrite was built to verify the correctness of the data to be deletion.Finally,the dual mechanism of changing the ciphertext access control policy and data overwriting guarantees the data assured deletion.The experimental analysis proves that the fine-grained control is better and the security is more reliable than the previous logical delete method in the assured deletion of data.